An Aneurysmal Bone Cyst in the Skull Base. Issue 7 (October 2017) - Kim, Sangjun; Jung, Dong Won; Pak, Min Gyoung; Song, Young Jin; Bae, Woo Yong
Abstract : Abstract: An aneurysmal bone cyst (ABC) is believed to be attributable to intraosseous circulatory disturbance. An ABC is a vascular tumor of the bone caused by bony expansion after partial vascular occlusion and congestion. Most ABCs are found in adolescents (approximately 75% of ABCs are observed in patients under 20 years of age). The most common ABC sites are the long bones of the limbs, the vertebrae, and the cranial bone. Aneurysmal bone cysts in the skull base or ethmoid sinus have been but rarely reported worldwide. The authors report on a patient with a very large ABC in the skull base and the ethmoid sinus; this was successfully managed by a neurosurgeon.